Emergent Carotid Thromboendarterectomy for Acute Symptomatic Occlusion of the Extracranial Internal Carotid Artery - Gunka, Igor; Krajickova, Dagmar; Lesko, Michal; Jiska, Stanislav; Raupach, Jan; Lojik, Miroslav; Maly, Radovan (Vascular and endovascular surgery, 2017)
BACKGROUND: Strokes secondary to acute internal carotid artery (ICA) occlusion are associated with an extremely poor prognosis. The best treatment approach in this setting is still unknown. The aim of our study was to evaluate the efficacy, safety, and outcomes of emergent surgical revascularization of acute extracranial ICA occlusion in patients with minor to severe ischemic stroke. METHODS: A retrospective analysis was performed using prospectively collected data of consecutive patients who underwent carotid thromboendarterectomy for symptomatic acute ICA occlusion during the period from January 2013 to December 2015. Primary outcomes were disability at 90 days assessed by the modified Rankin Scale (mRS) and neurological deficit at discharge assessed using the National Institute of Health Stroke Scale (NIHSS). Secondary outcomes were the recanalization rate, 30-day overall mortality, and any intracerebral bleeding. RESULTS: During the study period, a total of 6 patients (5 men and 1 woman) with a median age of 64 years (range: 58-84 years) underwent emergent reconstruction for acute symptomatic ICA occlusion within a median of 5.4 hours (range: 2.9-12.0 hours) after symptoms onset. The median presenting NIHSS score was 10.5 points (range: 4-21). Before surgery, 4 patients (66.7%) had been treated by systemic recombinant tissue plasminogen activator lysis. The median time interval between initiation of intravenous thrombolysis and carotid thromboendarterectomy was 117.5 minutes (range: 65-140 minutes). Patency of the ICA was achieved in all patients. On discharge, the median NIHSS score was 2 points (range: 0-11 points). There was no postoperative intracerebral hemorrhage and zero 30-day mortality rate. At 3 months, 5 patients (83.3%) had a good clinical outcome (mRS ≤ 2). CONCLUSION: Patients presenting with minor to severe ischemic stroke syndromes due to isolated extracranial ICA occlusion may benefit from emergent carotid revascularization. Thorough preoperative neuroimaging is essential to aid in selecting eligible candidates for acute surgical intervention.
Keywords: cévní mozková příhoda; Patient Selection; Brain Ischemia; časové faktory; outcome; výsledek terapie; Carotid Artery, Internal; perfuzní zobrazování; Cerebrovascular Circulation; arteria carotis interna; Retrospective Studies; Time Factors; čas zasáhnout při rozvinutí nemoci; CT angiografie; carotid artery occlusion; ischemie mozku; lidé; Thrombolytic Therapy; senioři nad 80 let; retrospektivní studie; Endarterectomy, Carotid; senioři; digitální subtrakční angiografie; Stroke; Computed Tomography Angiography; Risk Factors; mozková angiografie; mužské pohlaví; Acute Disease; Angiography, Digital Subtraction; Cerebral Angiography; Female; mozkový krevní oběh; Severity of Illness Index; akutní nemoc; acute ischemic stroke; carotid endarterectomy; Male; Carotid Stenosis; stenóza arteria carotis; Disability Evaluation; průchodnost cév; Emergencies; Vascular Patency; Aged, 80 and over; ženské pohlaví; internal carotid artery; Treatment Outcome; rizikové faktory; trombolytická terapie; Aged; penumbra; Perfusion Imaging; Humans; Time-to-Treatment; lidé středního věku; Middle Aged; posuzování pracovní neschopnosti; výběr pacientů; stupeň závažnosti nemoci; náhlé příhody; karotická endarterektomie